Adoption challenges of environmental monitoring practices: case study of temperature data loggers in selected Australian vegetable supply chains - Moudassir Habib; Ben Lyons; Chad Renando (Applied Water Science)
Abstract Temperature monitoring across cold chain practices is an integral component of fresh produce supply chains. Numerous temperature data loggers (TDLs) are available to reduce the significant amount of food loss and waste (FLW) (equivalent to around 50%) in vegetable supply chains; however, its widespread adoption remains a challenge for the actors along the chain. This study seeks to understand the adoption of TDLs within selected Australian vegetable supply chains to address the challenge of FLW. Three representative cases of vegetable supply chains were purposively selected, including growers, packers, transporters, distribution centres along with technology providers, and industry experts. Data were collected through semi-structured interviews and analysed utilising thematic analysis. The findings indicate that members of vegetable supply chains recognise temperature management as one of the key factors for preserving quality and extending shelf life of their produce; however, they are not proactively seeking to utilise TDLs in their supply chain operations. Resistance to adoption of TDLs is deeply rooted in product-based challenges such as cost and compatibility, and process-based challenges including information sharing and product mixing. Additionally, presence of an individual’s undesirable behavioural aspects such as status-quo bias and responsibility shirking as well as prevailing social norms within the industry influence the adoption of TDLs.